2022
DOI: 10.3390/cells11142246
|View full text |Cite
|
Sign up to set email alerts
|

A Drug Repurposing Screen Identifies Fludarabine Phosphate as a Potential Therapeutic Agent for N-MYC Overexpressing Neuroendocrine Prostate Cancers

Abstract: Neuroendocrine prostate cancer (NEPC) represents a highly aggressive form of prostate tumors. NEPC results from trans-differentiated castration-resistant prostate cancer (CRPC) with increasing evidence indicating that the incidence of NEPC often results from the adaptive response to androgen deprivation therapy. Recent studies have shown that a subset of NEPC exhibits overexpression of the MYCN oncogene along with the loss of tumor suppressing TP53 and RB1 activities. N-MYC is structurally disordered with no b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 73 publications
1
5
0
Order By: Relevance
“…Our study revealed that treatment with fludarabine elicited the most pronounced transcriptional changes, exhibiting a large number of differentially expressed genes that converge on p53 pathway signaling and Myc transcription factor activity. Fludarabine treatment is known to induce a p53-dependent transcriptional responses in chronic lymphocytic leukemia (45,46), and our study highlights a similar mechanism of action in an additional hematological malignancy model. Although we observed only minimal overlap in differentially expressed genes between the scRNA-seq method, of the genes identified, DDB2 , was consistently detected by all three methods and is known to be induced by p53.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Our study revealed that treatment with fludarabine elicited the most pronounced transcriptional changes, exhibiting a large number of differentially expressed genes that converge on p53 pathway signaling and Myc transcription factor activity. Fludarabine treatment is known to induce a p53-dependent transcriptional responses in chronic lymphocytic leukemia (45,46), and our study highlights a similar mechanism of action in an additional hematological malignancy model. Although we observed only minimal overlap in differentially expressed genes between the scRNA-seq method, of the genes identified, DDB2 , was consistently detected by all three methods and is known to be induced by p53.…”
Section: Discussionsupporting
confidence: 67%
“…We additionally detected a consistent downregulation of Myc transcriptional targets in fludarabine-treated cells. A recent drug repurposing effort found fludarabine phosphate to suppress MYCN signaling in neuroendocrine prostate cancers (46). These findings motivate further exploration of MYC transcriptional activity as a biomarker of response to fludarabine and other DNA synthesis inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…We additionally detected a consistent downregulation of Myc transcriptional targets in fludarabine-treated cells with the MULTI-seq and 10x Fixed approaches. A recent drug repurposing effort found fludarabine phosphate to suppress MYCN signaling in neuroendocrine prostate cancers ( 49 ). These findings motivate further exploration of MYC transcriptional activity as a biomarker of response to fludarabine and other DNA synthesis inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, KRAS signaling mediated by the phosphatidylinositol 3-kinase (PI3K) effector pathway leads to activation of the AKT kinase and subsequent inactivation of GSK3, thereby stabilizing MYC ( 79 ). Consequently, AKT signaling inhibition leads to MYC protein destabilization as shown with the drug fludarabine phosphate, which was identified in a drug-repurposing screen on neuroendocrine prostate cancer cells ( 94 ). These cells are derived from a highly aggressive prostate cancer form featured by MYCN overexpression and loss of the tumor suppressors TP53 and RB1.…”
Section: Myc: An Oncogenic Transcription Factor With Pleiotropic Func...mentioning
confidence: 99%
“…These cells are derived from a highly aggressive prostate cancer form featured by MYCN overexpression and loss of the tumor suppressors TP53 and RB1. Fludarabine phosphate was identified to inhibit cell proliferation by inducing reactive oxygen species (ROS) and by inhibiting AKT signaling, thereby affecting NMYC protein stability and the expression of NMYC target genes ( 94 ).…”
Section: Myc: An Oncogenic Transcription Factor With Pleiotropic Func...mentioning
confidence: 99%